Pengembangan Instrumen Penilaian Terintegrasi untuk Mengukur Keterampilan Berpikir Analitis dan Sikap Ilmiah siswa pada materi kesetimbangan Kimia - Lalu Busyairi Muhsin; Endang Widjajanti Laksono (Postgraduate, University of Mataram, 2023)
Technological advances which are the parameters of the new era have an impact on the demands for increasing skills. The current demand for skills is in the form of 21st century skills, including analytical thinking skills. In addition, scientific attitudes are part of the science elements that are required to be mastered by students in this century, therefore it is necessary to have an instrument that can measure these two skills, based of this, an integrated assessment instrument is developed which aims to determine the characteristics of the instrument, the feasibility and the results of the measurement of an integrated assessment of students' analytical thinking skills and scientific attitudes on chemical equilibrium material for 11th grade of senior high school. All test subjects came from six schools in the city of Mataram, West Nusa Tenggara province. Sample take by stratified random sampling technique. The test results were analyzed using the Partial Credit Model 1 Parameter-Logistic (PCM 1-PL) approach in Item Response Theory (IRT) by the Winsteps program. All items were declared fit. The measurement results using this integrated assessment instrument show that students' analytical thinking skills and scientific attitudes on chemical equilibrium material are 36.5% in the moderate category